Depressive symptoms in students at a border university - Rosalina Marques Baia; Fernanda Matos Fernandes Castelo Branco; Renan Alves Silva (O Mundo da Saúde, 2020)
Depression is a contemporary disease whose silent symptoms are often barely noticeable in academic life. The objective of this study was to analyze the prevalence of depressive symptoms in academics at a border university. This was a cross-sectional, descriptive study, carried out with 233 students, from the various existing courses, regularly enrolled in a university located in the Brazilian Amazon. For data collection, a self-administered questionnaire, prepared by the researchers themselves, structured with closed questions, contemplating the sociodemographic variables, educational, clinical and behavioral aspects was used first; and to survey depressive symptoms, the Beck Depression Inventory (BDI) was applied. The results showed a predominance of young adults (82.4%), aged between 20 and 40 years old, female (58.6%), single (51.9%), evangelical (39.9%), who performed academic activities concomitantly with the remunerated ones (59.7%). BDI indicated that 53% of respondents were without depression/minimal symptoms, 31.6% had symptoms of mild depression; 13.2% had signs of moderate depression, and 2.2% had severe depression. A higher index of depressive symptoms was speculated among the investigated students, due to the physical and social conditions of the studied field, therefore, the result was antagonistic to the hypothesis of this study. It is believed that, in spite of the low rates, there is a need for an in-depth reflection on improvements in the psycho-pedagogical support given to students, in the dissemination of the service provided in the psychological sector of the campus, in order to further reduce the percentage of depressive levels and foster appropriate strategies for coping with problems related to academic life